School Reform: Lessons from the Departed - Marshall, J. Dan; Valle, James P. (Education Policy Analysis Archives, 1996)
In this article, the authors present data from a small study of 19 families who educate their children at home in rural Pennsylvania. Findings relative to why they opted out of the public education system and whether they would return are analyzed in light of a previously established construct (Idealogue/Pedagogue) before being used to critique and expand it in light of broader cultural concerns. The authors argue, overall, that home educators are asserting their historical option of cultural agency and schooling. (Note 1) If "school reform" is a bandwagon, then the parade is still in progress. Most of the grand proposals earlier composed by politicians, pundits, policy wonks, and professors have evolved into smaller, more locally pertinent endeavors by actual change participants (educators, students, parents and community members). In the worst case, the continuing accumulation of school reform efforts is understood as succeeding waves of perpetual hassle and silliness which disturb the basic soundness of business-as-usual. In the best case, such efforts become a representation of participants' commitment to the repetitive nature of the learning process: desiring to know and understand - acting upon these desires - making sense of and reflecting upon those actions - identifying new or different desires to know and understand. Thus, in the best case, school reform efforts should be here to stay. Those who care about examining and acting upon the quality of their local schools seek information from numerous sources, including their own experiences, outside consultants, beliefs and opinions collected from local, state, and national polls, and "the literature" of academia. But they seldom tap the one segment of their community which may provide the most unique perspective: parents who have opted out of the local public school system. We suspect that this group – particularly those families who have taken it upon themselves to provide education at home – may have something important to offer those working to change public education. In this article, we discuss our preliminary foray into the lives of several Pennsylvania home educators in light of public school reform efforts.